A role for confidence: volition regimes and news - SACCAL, Alessandro (Journal of Mathematical Economics and Finance; Vol 9 No 1 (2023): JMEF, Volume IX, Issue 1(16), Summer 2023, 2023)
The economic literature presents a variety of empirical models of the structural impulse response function (SIRF) in real consumption and real output following changes in confidence or sentiment, particularly in the US and EA. This paper replicates them on the orbit of a neokeynesian dynamic stochastic general equilibrium (NK-DSGE) model characterized in particular by macroeconomic agents and derived from start to finish. Trust is specifically modeled as an endogenous variable characterized by a coalescence of three processes governed by a degree of volition, the processes being permanent technology, transient technology, and noise technology. The first two processes affect the actual production technology with a delay of one lag, while the third does not at all. The short-run responses to changes in confidence are shown whenever the degree of willingness allows confidence to change real consumption and aggregate labor, thus being non-negligible. Whenever the degree of volition was, by contrast, negligible, exogenous shocks in noise technology would cause no fluctuation in actual consumption and actual power.